THE INFLUENCE OF COMPETENCE, MOTIVATION AND REWARD ON EMPLOYEE PERFORMANCE WITH WORK SPIRIT AS AN INTERVENING VARIABLE - Dewi Darma Sary Tarigan; Mesra .B; Kiki Farida Ferine (Yayasan Multidimensi Kreatif, 2026)
This study aims to analyze the effect of competence, motivation, and rewards on employee performance with work spirit as an intervening variable at the Regional Office of the Directorate General of Immigration of North Sumatra. The problem addressed in this study is the importance of improving employee performance in responding to increasingly complex public service demands, which are influenced by competence, motivation, rewards, and work spirit. This study employed a quantitative approach with an explanatory research design. The population consisted of all employees at the Regional Office of the Directorate General of Immigration of North Sumatra. Data were collected through questionnaires, while data analysis was conducted using the Partial Least Squares–Structural Equation Modeling (PLS-SEM) method with the assistance of SmartPLS software. The results indicate that competence has a positive and significant effect on employee performance (β = 0.290; p = 0.006) and work spirit (β = 0.223; p = 0.029). Motivation has a positive and significant effect on employee performance (β = 0.479; p = 0.001) and work spirit (β = 0.398; p = 0.003). Rewards also have a positive and significant effect on employee performance (β = 0.411; p = 0.008) and work spirit (β = 0.375; p = 0.001). However, work spirit does not have a significant effect on employee performance (β = -0.184; p = 0.128). Furthermore, work spirit is unable to mediate the effects of competence, motivation, and rewards on employee performance. The R-Square values indicate that competence, motivation, rewards, and work spirit explain 96.9% of the variance in employee performance, while competence, motivation, and rewards explain 97.0% of the variance in work spirit.The study concludes that competence, motivation, and rewards are important factors that directly improve employee performance. Meanwhile, work spirit was not proven to function as an intervening variable in the relationship between competence, motivation, rewards, and employee performance at the Regional Office of the Directorate General of Immigration of North Sumatra